Redesigning grade school libraries of the University of the Philippines Integrated School (UPIS) in the University of the Philippines Diliman in the 21st Century - Faustino, Johanna Victoria A. (University of the Philippines Diliman, Integrated School, 2018)
Abstract: This case study aims to propose design solutions for the two library facilities of Grade School students belonging to the Generation Z(Gen Z), specifically kinder-Grade 2 and Grade 3 to 6 libraries of the University of the Philippines Integrated School (UPIS). the thrusts of the University of the Philippines, cohort of the students and the learning preferences of the Generation Z in the 21st century provide the framework in this study towards the proposal for designing the given spaces. In this study, focused group discussions with seven groups consisting of 5 students each were selected from contacts of employees from the UP College of Home Economics. Semi-structures interviews were conducted with the three personnel of the two libraries and the head librarian regarding their roles, perceptions, and concerns about the interiors of the existing library spaces. Site observations and photo documentation were also conducted to evaluate the existing physical conditions of the interiors of the libraries. Thirty-five (35) Gen Z students (from High School and College) in various schools, through the online survey, participated and were asked regarding their preferences on library spaces. Secondary sources from literature were used to supplement the findings of the study. Results show that majority of the student respondents still enjoy getting to the library as a study and learning space. Unavailability of the computers for use and lack of wifi connection, old books and discomfort experience due to warm temperature were some the reasons for dislike. Likewise, updated reading selection and available technology, audio/visual materials, better circulation and space layout, lighting, ventilation and additional staff were cited as points of improvement by the librarians. On the observations of the two libraries is that students often come and study in groups, which was also verified by the librarians who notice how students use the space. Attributes of the space such as layout, thermal comfort, sound, lighting, and materials used were considered in the proposed designs. Display is believed to play a substantial role on the engagement of the students to their learning environment, as this may affect their preferences for visibility and accessibility. Sensorial factors include touch, olfactory, auditory, and visual aspects, and the integration of innovation strategies into the library, such as having clustered spaces of individual learning, group activities , touch through educational interactive materials, improved computer stations, music area with headphones and bilingual wayfinding solutions were proposed in the designs. This study only proposes several options for the interior design of the two libraries, for consideration of the UPIS administration, and does not include design stages after schematics. It is also recommended for interior spaces in the University to reflect more the spirit of nationalism and pride of place of being in UP in the libraries, and to consider sustainability in the design considerations. This study drew out that a library design may evolve and create more dynamism if the needs and preferences of the age group that will use the spaces, aside from the inputs of the administration, personnel and faculty.